Ecological-cenotic and floristic analysis of Dactylorhiza fuchsii(Druce) Soo populations in the Kazakhstan part of the Altai mountain country - Sumbembayev А.А.; Danilova, A.N.; Premina, N.V.; Matveeva, E.V. (Fundamental and Experimental Biology, 2022)
The purpose of this work is to conduct an ecological-cenotic and floristic analysis of the Dactylorhiza fuchsii (Druce) Soo populations in the Kazakhstan part of the Altai mountain country, to determine the ecological optimum and plasticity of the species in the surveyed communitiesbased on the similarities and differences of phytocenoses. The materials were obtained as a result of a survey of the territory using the route-reconnaissance method. Based on field studies in the surveyed region, four main populations were identified, 12 localities were marked. It was found that the coenoflora of D. fuchsiipopulations in the Kazakhstan part of the Altai mountain country was formed by 251 species belonging to 49 families, 155 genera. Typical marker species are Betula verrucosa, Juncus compressus, Poa palustris, Poa pratensis, Filipendula ulmaria, Geum rivale, Sanguisorba officinalis. The coenoecotypes occupy wet meadows, edges of birch and mixed forests, river valleys and streams with inhomogeneous moisture and rich humus substrate. The floropopulation similarity of the studied populations varies within 12–24 %. Ecologically, in all populations, the basis of phytocenoses is made up of mesophytes —74 %, the share of mesohygrophytes —18 %, xeromesophytes —8 %. Herbaceous plants dominate in the composition of life forms —219 species (87 %). The tree-shrub flora is poorly represented —32 species (13 %). Self-maintenance and reproduction of the species are carried out by seeds. The ecological optimum of D. fuchsiifalls on the Calamagrostis-heteroherba, Filipendula —Sonchus —Equisetum, Allium — Dactylis —Phleum, Equisetum —Festuca —Agrostis, Betula —Carex phytocenoses.